The Effect of Compliance With The School of Norma (Code of Conduct) School To The Discipline of Students Even Semester Even MTs Ibrahimy At Calipuro Banyuwangi, East Java, Indonesia - Misdi R, Ayip; Listiwikono, Eko (International Journal for Educational and Vocational Studies, 2020)
In accordance with government policy, education is essentially as an effort to prepare students to deal with an ever-changing environment, and education basically aims to improve the quality of life and life of the community. Fostering school discipline is one form of teacher work in schools in the context of fostering the younger generation and the formation of disciplined and educated people. Therefore the rules are very useful for the younger generation, especially for students who are in the school environment so that they will become a generation of discipline, educated and become the pride of the school, parents, nation and state. This study only discusses what influences student learning discipline, namely adherence to school norms, so this is used as a study of the effect of adherence to school norms (discipline) on student discipline, even semester MTs Ibrahimy Distric Kalipuro Banyuwangi.In determining the area, researchers used a regional purposive method. This research takes place in the research at MTs Ibrahimy Distric Kalipuro Banyuwangi. The methods used by the authors in this study are: 1) Observation Method, 2) Interview Method, 3) Documentary Method, 4) Questionnaire Method. In this study the authors use a statistical analysis method, where this analysis seeks to present the preparation, analyzing data from the results of the study in the form of numbers both in tabular and graphical form. Based on calculations that the empirical chi value of = 1,011 consulted X ² based on a 5% significance level in the table db = 1 (K-1) (K-1) = 3.841 it turns out that after comparing with chi squared (X²) calculation is greater chi squared table . So that in this study there is no effect of adherence to school norms (discipline) on the discipline of students studying even semester MTs Ibrahimy Distrik Kalipuro Banyuwangi.